2015
DOI: 10.1007/s00209-015-1437-4
|View full text |Cite
|
Sign up to set email alerts
|

Compactness properties of commutators of bilinear fractional integrals

Abstract: Commutators of a large class of bilinear operators and multiplication by functions in a certain subspace of the space of functions of bounded mean oscillations are shown to be jointly compact. Under a similar commutation, fractional integral versions of the bilinear Hilbert transform yield separately compact operators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…We would like to point out that the conclusion of Theorem 3.1 holds also for the iterated commutator [[I α , b 1 ] 1 , b 2 ] 2 of the bilinear fractional integral I α with the same indexes, which is defined by Recently, Bényi et al [8] proved that if 0 < α < 2n, 1 < p 1 , p 2 < ∞ with 1 p 1 + 1 p 2 > α n , 1 < q < ∞ with 1 q = 1 p 1 + 1 p 2 − α n , then for b ∈ CMO, [I α , b] i (i = 1, 2) are all compact operators from L p 1 (R n ) × L p 2 (R n ) to L q (R n ).…”
Section: Remark 31mentioning
confidence: 94%
“…We would like to point out that the conclusion of Theorem 3.1 holds also for the iterated commutator [[I α , b 1 ] 1 , b 2 ] 2 of the bilinear fractional integral I α with the same indexes, which is defined by Recently, Bényi et al [8] proved that if 0 < α < 2n, 1 < p 1 , p 2 < ∞ with 1 p 1 + 1 p 2 > α n , 1 < q < ∞ with 1 q = 1 p 1 + 1 p 2 − α n , then for b ∈ CMO, [I α , b] i (i = 1, 2) are all compact operators from L p 1 (R n ) × L p 2 (R n ) to L q (R n ).…”
Section: Remark 31mentioning
confidence: 94%
“…Compactness results in the multilinear setting have just began to be studied. Bényi et al [3], [4] and [6] showed that symbols in CMO again produce compact commutators. Ding and Mei [20] consider the compactness of linear commutator of bilinear operators from product of Morrey spaces to Morrey spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Also, let CM O(R n ) be the closure in the BM O(R n ) norm of C ∞ c (R n ), which represents the space of infinitely differentiable functions with compact support. The boundedness and compactness of [b, I α ] i on variant function spaces have been the topic in many articles recently, see [1,2,3,5,6,12,13,17,18,19,26], among numerous references. One of the interesting questions on [b, I α ] i is whether it can be used to characterize BM O(R n ) by boundedness, or CM O(R n ) by compactness, as those in the linear setting (see [7,9,27] etc).…”
Section: Introductionmentioning
confidence: 99%